2000
DOI: 10.1097/00000421-200008000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Treatment of Advanced Gastric Cancer With Docetaxel and Granulocyte Colony-Stimulating Factor (G-CSF)

Abstract: We conducted a phase II study to evaluate the efficacy and tolerance of docetaxel monotherapy with granulocyte colony-stimulating factor (G-CSF) support in patients with advanced gastric cancer. Thirty patients with measurable advanced gastric cancer were enrolled. Twenty-four patients were chemotherapy-naive and six patients had previously received adjuvant chemotherapy after complete surgical resection. Docetaxel was administered at 100 mg/m2 IV during 1 hour every 3 weeks. G-CSF 5 microg/kg SC was also give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 11 publications
1
47
0
Order By: Relevance
“…Recent phase II studies have established the role of docetaxel in first-line and second-line treatment of advanced gastric cancer (Sulkes et al, 1994;Furue and Taguchi, 1998;Mavroudis et al, 1999). As a consequence, the hope for more potent regimens prompted several investigators to evaluate docetaxel in multidrug regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phase II studies have established the role of docetaxel in first-line and second-line treatment of advanced gastric cancer (Sulkes et al, 1994;Furue and Taguchi, 1998;Mavroudis et al, 1999). As a consequence, the hope for more potent regimens prompted several investigators to evaluate docetaxel in multidrug regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Docetaxel has been tested in advanced gastric cancer and it showed promising single-agent activity with 20% to 24% response rates in treated and chemotherapy-naive patients (Sulkes et al, 1994;Furue and Taguchi, 1998;Mavroudis et al, 1999;Vanhofer et al, 1999). A logical step of investigation consisted in the development of multi-drug schedules including docetaxel and other known active drugs.…”
mentioning
confidence: 99%
“…Subsequent phase I and II clinical trials have confirmed that docetaxel is effective in advanced gastric cancer when used as monotherapy, yielding response rates of 20%-24% [11][12][13]. In addition, docetaxel given as first-line treatment, with granulocyte colony-stimulating factor (G-CSF) as support, has been shown to be both active and well tolerated [14].…”
Section: Introductionmentioning
confidence: 99%
“…New cytotoxic agents, such as irinotecan, paclitaxel and docetaxel could be a more appealing approach for the treatment of advanced gastric cancer (Kollmannsberger et al, 2000;Mavroudis et al, 2000;Roth et al, 2000). Docetaxel obtained a 20% response rate as first-line treatment in 37 advanced gastric patients (Sulkes et al, 1994) with a median survival time of 7 months.…”
Section: Discussionmentioning
confidence: 99%